A total systems design on Cravings Eco Center of the Cravings Group of Company - Gigante, Mary Ann C.; Lebuna, Imee Claire C.; Patio, Ma. Katrina M.; Silva, Ramona E.
This study focused on improving the Cravings Group of Companies through a Total Systems design of its Eco Center which exists for the purposes of supplying organic vegetables for the its restaurants. Vegetables bought by the Cravings Group Purchasing Department from the Eco Center are marked down at a 30% discount. Currently, less than 4% of the vegetables demand was provided by the Eco Center which is low compared to the 50% target set by the company. This results to an estimated PhP 22,000 monthly opportunity cost for the Purchasing Department and PhP 39,268 loss for the Eco Center. Initial analysis of the whole Cravings Group was conducted through a per department study of the Cravings Group. The data were gathered through interviews with head of each department and conduct of additional research. Several problems such as late deliveries of commissary products and supply stock-outs were determined. It was later revealed to the proponents of this study that the company has already decided to build new facilities to address these problems. Taking that into consideration, the project was scoped to cover the low productivity problem of the Eco Center. Interviews with the officer-in-charge of the Eco Center were done regularly throughout the duration of the study with consultations from the Head of the Purchasing Department. Capacity Planning and Scheduling was done in order to maximize the use of the area. First, the available plots were measured to determine the capacity of the area. Afterwards, the yield per square meter per plant was determined through random sampling of available vegetables and additional internet research. The length of time to harvest was determined through the historical data and research. The demand analysis was done by referring to the data provided by each of the Cravings Group food establishments. Plants to be cultivated in the area were chosen based on their demand and the other criteria such as the expected annual revenue per square meter. The result is 110% increase in the revenue of the Eco Center and savings of the Purchasing Department. This translates to a PhP 17,076 profit of the Eco Center and PhP 26,078 savings of the Purchasing Department per month. To further improve the productivity of the Eco Center, Design for Safety and Reliability was performed as well as the preparation of documentation forms.